Desain Aplikasi Administrasi Untuk Mengontrol Pemesanan Barang Pada Percetakan - Grace Gata; Lilis Kurniawati (Sekolah Tinggi Teknik - PLN, 2016)
Printing activity is carried out in a printing business entity in doing custom production is obtained, after it is done printing to meet pelanggan needs customized with options specified. The printed form of business cards, banners, letters Yasin, invitations and others in the business process run using documents such as the memorandum, permit, register printed matter and the income statement. In fulfilling pelanggan orders is often the case due to frequent delays in the printing of the memorandum were tucked, difficult in checking the repayment when the reservation is made and the time of the return of printed material that could not be regulated properly. The purpose of this study to detect delays and overcome the difficulties in checking the repayment and can be made a more detailed report to be able to support control and data revenues. The methodology used by the UML (Unified Modeling Language) with a mix of fishbone in determining problems, programming languages ​​with Visual.net and database built on MySQL.